MO886ASSESSMENT OF HEALTH-RELATED QUALITY OF LIFE IN PATIENTS ON HEMODIALYSIS USING RAND36 SCORE. (29th May 2021) - Dassi, Manisha; Janardhana, Anupama; Hegde, Sampoorna; Aggarwal, Garima; Namagondlu, Girish; A, Kishan; Penmatsa, Krishnam Raju; Langote, Amit; Balasubramanium, Karthikeyan; Conjeevaram, Arvind
Abstract: Background and Aims: Evaluation of Health-related quality of life (HRQoL) is an important, albiet neglected component of health care in patients with End Stage Renal Disease (ESRD). RAND-36 is a validated scoring system for evaluating HRQoL. Patients on hemodialysis experience decrease in various aspects of HRQoL. Various disease related and socio-economic factors influence HRQoL. There is limited data on HRQoL among patients of ESRD on hemodialysis from Indian subcontinent. In the present study, we aim to evaluate the HRQoL using RAND-36 score & the factors which influence it's various aspects. In addition, we aim to evaluate patient perception of ease of access to dialysis related health care and its impact on RAND-36 score. Method: This cross sectional, multi-centric study was performed in Nov 2020. A random sampling was employed to select the study participants. Patients with history of psychiatric illness, significant impairment of hearing, speech, or cognitive disturbances were excluded. RAND 36-Item Health Survey (Version 1.0) was used and circulated amongst dialysis patients across 10 dialysis centres in hospitals across India. Final scores were calculated using standard guidelines. A proprietary software from Bloom Value Corporation was used for data capture by electronic means and Power BI was used for analysis. Results: 257 ESRD patients on hemodialysis completed the survey. Mean age was 52.9 years. 65.4 % participants were males, 39.69% were Diabetics and 75.88% had hypertension. Accessibility to healthcare was reported by 36% and 27.7% patients as 'excellent' and 'very good' respectively. The mean scores in various scales were Physical Functioning (PF) 47.27±27.87 %, Role limitations due to physical health (RP) 54.18 ± 40.97 %, Role limitations due to emotional problems (RE) 55.38 ± 43.57 %, Energy/fatigue (EF) 49.80 ± 19.38 %, Emotional wellbeing (EW) 57.71 ± 22.04 %, Social functioning (SF) 58.02 ± 25.32%, Pain (BP) 68.28 ± 23.52 % and General Health (GH) 48.11 ±16.43%. Lower PF Scores were seen with higher age (NS), ≥ 2 comorbidities (NS). PF scores were higher in patients with Government insurance and higher perception of healthcare accessibility (NS). RP Scores were higher in males and with advancing age (NS). Employed patients had lower RP scores (p=0.009). RE scores were lower in patients with ≥ 2 comorbidities (NS) and among Employed patients (p=0.04). EF Scores were higher in males (p=0.07) and lower in patients with ≥ 2 comorbidities (NS). EW scores were higher in males (p=0.09) and among patients with higher perception of healthcare accessibility (NS). SF Scores were higher in males (p=0.08) and with higher perception of healthcare accessibility (NS). BP Scores were higher among patients with≥ 2 comorbidities (p=0.04) and higher perception of healthcare accessibility (NS). GH scores were higher with Government Insurance availability and higher perception of healthcare accessibility (NS). Conclusion: To our knowledge this is the first multi-centric study conducted amongst ESRD patients in India, evaluating HRQoL using RAND36 scores. There is significant heterogeneity in patient reported outcomes and it's determinants. Government Insurance support and a higher perception of healthcare availability have positive impact on many aspects of HRQoL. This is a valuable tool in executing patient centred care.